2016
DOI: 10.1007/s00299-015-1924-4
|View full text |Cite
|
Sign up to set email alerts
|

LcGST4 is an anthocyanin-related glutathione S-transferase gene in Litchi chinensis Sonn.

Abstract: A novel LcGST4 was identified and characterized from Litchi chinensis . Expression and functional analysis demonstrated that it might function in anthocyanin accumulation in litchi. Glutathione S-transferases (GSTs) have been defined as detoxification enzymes for their ability to recognize reactive electrophilic xenobiotic molecules as well as endogenous secondary metabolites. Anthocyanins are among the few endogenous substrates of GSTs for vacuolar accumulation. The gene encoding a GST protein that is involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 46 publications
7
90
0
Order By: Relevance
“…Heterologous overexpression of VviGST4 ( Vitis vinifera ) and AcGST1 ( Actinidia chinensis ) in Arabidopsis tt19 mutant can functionally complement both the anthocyanin‐less phenotype in plant and the PA‐deficient phenotype in seed coat (Liu et al , ; Pérez‐Díaz et al , ). However, in this study, PpGST1 only possessed the capacity to functionally complement the anthocyanin‐less phenotype of Arabidopsis tt19 mutant but not the PA‐deficient phenotype in the seed coat, which was similar to the result of An9 ( Petunia hybrida ), LcGST4 ( Litchi chinensis ), RAP ( Fragaria ananassa ), CsGSTF1 ( Camellia sinensis ) and MdGSTF6 ( Malus domestica ) in the tt19 complementation assay (Hu et al , ; Jiang et al , ; Kitamura et al , ; Luo et al , ; Wei et al , ). These data indicated that PpGST1 plays a pivotal role in anthocyanin transport and differed from AtTT19 , VviGST4 and AcGST1 which also participate in seed deposition of PAs.…”
Section: Discussionsupporting
confidence: 73%
“…Heterologous overexpression of VviGST4 ( Vitis vinifera ) and AcGST1 ( Actinidia chinensis ) in Arabidopsis tt19 mutant can functionally complement both the anthocyanin‐less phenotype in plant and the PA‐deficient phenotype in seed coat (Liu et al , ; Pérez‐Díaz et al , ). However, in this study, PpGST1 only possessed the capacity to functionally complement the anthocyanin‐less phenotype of Arabidopsis tt19 mutant but not the PA‐deficient phenotype in the seed coat, which was similar to the result of An9 ( Petunia hybrida ), LcGST4 ( Litchi chinensis ), RAP ( Fragaria ananassa ), CsGSTF1 ( Camellia sinensis ) and MdGSTF6 ( Malus domestica ) in the tt19 complementation assay (Hu et al , ; Jiang et al , ; Kitamura et al , ; Luo et al , ; Wei et al , ). These data indicated that PpGST1 plays a pivotal role in anthocyanin transport and differed from AtTT19 , VviGST4 and AcGST1 which also participate in seed deposition of PAs.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies indicated that the expression of LcUFGT , LcF3H , LcDFR , LcGST , and their regulatory gene LcMYB1 were up-regulated as the fruit developed toward full maturity (Wei et al, 2011; Lai et al, 2014; Li et al, 2015; Hu et al, 2016). In the present study, the expression of miR156a was enhanced with the accumulation of anthocyanins, while its target genes LcSPL1 / 2 were opposite ( Figures 3C,D ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the delicious taste, attractive red skin of litchi is another important aspect of the fruit quality. Recently, the gene involved in anthocyanin biosynthesis and sequestration from litchi has been reported (Wei et al, 2011; Lai et al, 2014, 2015, 2016; Li et al, 2015; Hu et al, 2016). However, the mechanism of miRNAs regulating anthocyanin biosynthesis in litchi has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AtTT2 regulates the expression of the MATE transporter gene TT12 to control the flavonoids transport41, and the maize ABC transporter ZmMRP3 involved in anthocyanin transport is regulated by the R (bHLH family) and C1 (R2R3-MYB) TFs35; and anthocyanin-related glutathione S-transferase gene LcGST4 was activated by LcMYB1, a key R2R3-MYB transcription factor that regulates anthocyanin biosynthesis in litchi35. Most of TFs are positive regulators in flavonoid biosynthesis, whereas a few of them have been identified as repressors in flavonoid pathway42. In our study, we first identified 42 MYB unigenes (19 up-regulated and 23 down-regulated) from the DEGs.…”
Section: Discussionmentioning
confidence: 99%